PRIMARY PRODUCTIVITY IN RIVER GODAVARI - Rajyalakshmi, T; Premaswarup, T V (Indian Journal of Fisheries, 2011)
Extensive investigations have been conducted on primary productivity inmarine environments and in lakes. But investigations in the flowing fresh waters,such as streams and rivers, are very few. Odum (1956, 1957) calculated theprimary productivity of thermal springs using diurnal changes in dissolved-oxygenconcentration. Owen (1965) while determining productivity detailed some of^e factors involved in the dissolved-oxygen distribution of the streams.